Fiscal Transition in Countries of the Former Soviet Union : An Interim Assessment - Davis, Jeffrey (IMF Working Papers; Working Paper ;, 1996)
This paper reviews the uneven record of fiscal performance in the states of the former Soviet Union since independence. Deficits have come down rapidly, an important contribution to stabilization. Given, however, the unexpectedly severe revenue decline and limited financing, the stabilization was reached by sharp cuts in expenditure. The cuts were abrupt and not focused on transition goals, and the instruments used vitiated normal budgetary processes. Hence, benchmarks of fiscal success other than stabilization are elusive. Government intervention and subsidies remain important, social spending is inefficient, and there is little evidence in the budget of restructuring.